Exploring interactive strategies for addressing reading difficulties in english subject among standard six pupils in Tanzania: Insights from public schools in Kongwa District - Ngonyani, Ebby; Matete, Rose Ephraim; Kashaigili, Johaiven Joel (Papanda Publisher, 2025)
This study investigates effective strategies for addressing reading difficulties among standard six pupils in English. It was informed by interpretivism philosophy with qualitative research methodology. Interview were used in data collection, that was then analyzed thematically. Findings reveal the significance of employing both interactive and direct instructional methods. Interactive strategies, such as group reading and collaborative discussions, facilitate peer modeling and enhance comprehension through shared learning experiences. Direct strategies, particularly questioning techniques, promote critical thinking and active engagement with texts. Additionally, the study highlights the importance of creating supportive learning environments that incorporate motivational practices, diverse reading materials, and technology. Regular assessments and tailored feedback are essential for identifying specific challenges and adapting teaching methods. The results indicate that a multifaceted approach, combining various instructional strategies and fostering a motivational atmosphere, significantly improves reading comprehension and develops a positive attitude towards reading among struggling students. Ultimately, the research underscores the need for educators to implement comprehensive, inclusive strategies to enhance literacy outcomes in the classroom.